The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3897/bdj.9.e65199
|View full text |Cite
|
Sign up to set email alerts
|

Liverwort flora of Ayan – a gained link between subarctic and hemiboreal floras in West Okhotiya (Pacific Russia)

Abstract: The liverwort flora of Ayan was first investigated one hundred and fifty years after the first exploration of vascular plants. A number of factors has determined the relatively high taxonomic diversity of liverworts in this hemiarctic flora of small-sized area: 118 species and one subspecies were revealed. These data are new not only for the studied area, but also for the huge land adjacent to the western coast of the Sea of Okhotsk. The liverwort flora possesses the domination of taxa common in the hemiarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Here we can find a contrast in distribution patterns between mosses and hepatics. The analysis of Bakalin et al (2021) found Ayan liverwort flora to be especially similar to Northern Sikhote-Alin, then Southern Sikhote-Alin, and then Northern Hokkaido. For mosses, the Northern Sikhote-Alin is enriched by temperate elements (Fedosov et al, 2016) even more than the Upper Bureya moss flora, and in Southern Sikchote-Alin and then Northern Hokkaido 'Arcto-Tertiary disjuncts' their number still increased.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Here we can find a contrast in distribution patterns between mosses and hepatics. The analysis of Bakalin et al (2021) found Ayan liverwort flora to be especially similar to Northern Sikhote-Alin, then Southern Sikhote-Alin, and then Northern Hokkaido. For mosses, the Northern Sikhote-Alin is enriched by temperate elements (Fedosov et al, 2016) even more than the Upper Bureya moss flora, and in Southern Sikchote-Alin and then Northern Hokkaido 'Arcto-Tertiary disjuncts' their number still increased.…”
Section: Discussionmentioning
confidence: 97%
“…Fieldworks were conducted by KK and VB over a total of three weeks in late June -early July of 2019, addressed specifically to liverwort exploration (Bakalin et al, 2021); however, mosses where gathered whereever possible, and 350 moss specimens were collected.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is a chain of disconnected islands that has never been a single land bridge between two continents and a place for the preservation of more southern species in shelters because of insularity. For various groups of plants in the Commander Islands, it is possible to find representatives of either endemic plants or those with locations that are remarkably distant from the main area body [ 13 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ecological habitat of K. beringii is not unusual in terms of the commonness of habitats on both the Commander Islands [ 17 , 18 ] and the Aleutians as a whole [ 19 ]. This is a wet, slightly shaded cliff along the seacoast.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptocolea imbricata was described by Schuster (1969) from an isolated location in Minnesota and then recorded by him from one station in Michigan and many localities in Ellesmere Island and Greenland (l. c.). The species was later found in Alaska (Steere and Inoue, 1978), Northwest Territories of Canada (Damsholt, 2007), a single locality in Europe (northern Sweden, Schuster & Mårtensson, 1978), one in Svalbard (Frisvoll & Elvebakk, 1996) and many localities in Asia, including its northern part , Schuster & Konstantinova, 1996Fedosov et al, 2015;Fedosov et al, 2020;Konstantinova et al, 2023), mountains of Yakutia (Sofronova, 2018), South Siberia (Mamontov, 2013), and Far East of Russia (Bakalin, 2010, 2015, Bakalin et al, 2021 ( Fig. 6).…”
Section: Morphologymentioning
confidence: 99%